Revitalization of 16 Ilir Market: A Study of Government Policy from an Urban Economic Perspective - M. Rifki Rahman; Alfitri; Mega Nugraha (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The revitalization of Pasar 16 Ilir plays a strategic role in maintaining the competitiveness of traditional markets amidst the expansion of modern retail and the digitization of commerce. This study employs a qualitative descriptive approach with thematic analysis to explore the challenges, benefits, and revitalization strategies based on the rational model. The findings indicate that revitalization contributes to economic competitiveness, social sustainability, and improved market governance. The rational model was chosen to ensure that policy decisions are evidence-based and aligned with the Maximum Social Gain principle. The implementation of revitalization is currently in the phase of infrastructure improvements and governance reforms. This study recommends synergy between the government, market managers, and traders to ensure the sustainability of a competitive and inclusive trading ecosystem.